Endovaginal ultrasound-assisted pain mapping in endometriosis and chronic pelvic pain. (October 2013) - Yong, P. J.; Sutton, C.; Suen, M.; Williams, C.
<x xml:space="preserve">Abstract</x> The objective of this study was to determine if the combination of tenderness-guided endovaginal ultrasound and digital pelvic exam (i.e. EVUS-assisted exam) for preoperative pain mapping, in cases without nodules or endometriomas, increases sensitivity/specificity for laparoscopic findings. This was a retrospective review of women with chronic pelvic pain ± infertility with preoperative pain mapping exam prior to laparoscopy (n = 97, 2006–7). Predictor variables (EVUS-assisted exam vs digital pelvic exam alone, for pain mapping) were coded as tender vs non-tender. Primary outcome was findings on laparoscopy (e.g. endometriosis or adhesions) and was coded as abnormal vs normal. We found that EVUS-assisted exam had greater sensitivity (0.81, 95% CI: 0.70–0.89) for abnormal laparoscopy compared with digital pelvic exam alone (0.58, 95% CI: 0.46–0.69) (McNemar's test, p < 0.001). Specificity was limited for both types of pain mapping (0.22, 95% CI: 0.08–0.44 for EVUS-assisted; and 0.39, 95% CI: 0.20–0.61 for digital), with no significant difference (p = 0.13). In conclusion, in the absence of nodules or endometriomas, EVUS-assisted exam increases sensitivity, but with no benefit in specificity, for prediction of abnormal laparoscopy.